Pesquisa de anticorpos antigliadina e anticorpos antiendomísio classes IGA, em pacientes com doenças reumatológicas auto-imunes do ambulatório de reumatologia do Hostipital das Clínicas UFMG - Victor de Barros Koehne (2007)
A clinical study was carried out for investigating the prevalence of positive serologic tests for coeliac disease, particularly IgA and IgG classes antigliadine antibodies (AGA) and IgA class antiendomysium antibodies (EmA), in autoimmune rheumatologic disease patients followed in the Ambulatório de Reumatologia do Hospital das Clínicas da Universidade Federal de Minas Gerais, in Belo Horizonte.It has also been tried to evaluate the correlation between the positive serologic tests with the use of prednisone and immunosupressor medication. Patients presenting serologic tests suspected for coeliac disease underwent duodenal endoscopic biopsy and the collected material was examined by an expert pathologist. From November 2005 to March 2007, 190 adult and pediatric patients with previous rheumatologic diagnosis were evaluated, divided into groups as follows: systemic lupus erythematosus (LES) (n=69), rheumatoid arthritis (AR) (n=48), juvenile rheumatoid arthritis (ARJ) (n=32) and spondyloarthropathies (n=41). IgA AGA and IgG AGA research was carried out on all of them byimmunoenzimatic assay (ELISA) and EmA research by indirectimmunoflorescence, using human umbilical cord substract. There was no statistically significant difference among the four patients groups related to the IgA AGA and IgG AGA optical density readings. There was four positive sera (2.1%) for IgA AGA, all with negative results for IgG AGA and EmA, two of these from AR patients, one LES, one from ARJ. Three sera (1.6%) had positive results for IgG AGA, all with negative results for IgA AGA and EmA, one from LES patient, one from AR patient and one with spondiloarthropathy related to Crohns disease. All seven patientes presenting positive antigliadine antibodies tests underwent duodenal endoscopic biopsies. In the EmA research, the serum dilution in 1:2.5showed positive results for 94 patients (49.5%), and in the 1:5 dilution for 41 (21.6%). Eleven individuals had positive results for EmA in the 1:40 dilution, corresponding to three LES patients, four AR patients and four patients with spondiloarthropathies, and nine of these underwent duodenal endoscopic biopsy. All the biopsy material from the 16 patients studied was considered satisfactory for the histological analysis, and no significant changes were proved in the duodenal mucosa. All the positive sera for EmA had negative results for the IgA (tTG) tissueantitransglutaminase antibodies. The positive EmA was associated to higher optical density readings for IgA AGA, but there was no relation between positive EmA and IgG AGA optical density readings. The use of prednisone and immunossupressors wasnt related to the IgA AGA optical density readings, neither to the IgG AGA readings. The use of these medication, however, was related to less positive EmA. In conclusion, positive results for AGA IgA, AGA IgG or EmA did not imply in the presence of coelic disease in the studied population. Mores studies are required in order to estimate more accurately the prevalence ofthis disease in rheumatologic patients.